Between Propaganda and Freedom of Aesthetic Experience: Poetry Reading Events by Actor Laimonas Noreika in the Late Soviet Era - Rėklaitytė, Akvilė (Literatūra, 2025)
The article examines strategies for popularizing poetry in Soviet-era Lithuania and the ambivalence of their effectiveness. The first part reconstructs the institutional system of literary propaganda and its social context, focusing on poetry evenings – i.e., literary events where professional actors recited poetry – that became especially popular in late Soviet Lithuania. The second part analyzes the popularity of the actor Laimonas Noreika’s ‘literary concerts’ and the persuasiveness of his rhetoric in the context of the time. The sources used include archival documents from the Bureau for the Propaganda of Fiction of the Lithuanian SSR, Laimonas Noreika’s diaries, and contemporaries’ testimonies.Drawing on Jacques Rancière’s theory of the politics of aesthetics – which posits that aesthetics can reorganize sensible experience and awaken critical perception – it is concluded that the regime’s attempts to control moral education through poetry promotion had a dual effect: on the one hand, it reinforced poetry’s prestige and moral authority, serving as a substitute for religion; on the other hand, the dissemination of poetry – understood as a project of moral and aesthetic education – had an unintended ‘side effect’ since poetry texts, especially those of the classical canon, when suggestively read and performatively reinterpreted by actors, encouraged a more individual subjectivity (as a counterpoint to the anti-individualist mass society), along with a critical attitude toward reality, and thus could strengthen the expression of alternative will within society.
Keywords: soviet literary propaganda; poetry readings; Jacques Rancière; politics of aesthetics; Laimonas Noreika; emotional community